Analysis of Validity, Reliability, Difficulty Level, and Discrimination Power of Students’ Critical Thinking Skill Test on Phase F Fluid Materials in Senior High School - Nur Tasya Putri; Emiliannur Emiliannur (Physics Learning and Education, 2026)
A high-quality assessment instrument is one that provides data that reflects actual conditions, is consistent and reliable, demonstrates varying levels of difficulty, and has a good discrimination index. Therefore, this study aims to test the validity, reliability, difficulty level, and analytical power of the items used to assess students' critical thinking skills. This study is descriptive and evaluative. The subjects were 31 11th-grade students at SMA Negeri 2 Painan. The data collection method used was a test. The study results indicated that for Grade XI, 17 test items were deemed valid, whereas 1 item was invalid. The reliability coefficient for Grade XI was 0.877, demonstrating that the test instrument is reliable. Regarding difficulty level, all 18 items were classified as difficult. In terms of discrimination power, 5 items fell into the poor category, while 13 items were categorized as fair. Based on the analysis of physics test items on the topic of fluids for the 2024/2025 academic year at SMA Negeri 2 Painan, it was concluded that the 11th-grade test items were valid and reliable. This indicates that the test items can be used as an evaluation tool.